TEACHERS ON INFORMATICS AS A COMPETENT SYSTEM ADMINISTRATOR - Khachirov, T. (Journal of Information Technologies in Education (ITE), 2010)
The article covers the important aspects of training information technologies teachers in the field of communication technologies, considered the possibility of using terminal technologies and virtualization technologies in educational process.